Analisis Tingkat Kognitif Latihan Soal Berdasarkan Taksonomi Bloom pada Buku Teks Fikih Kelas IV Kurikulum 2013 - Rahmat Rudianto; Isnaini Aprilia (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2020)
The practice questions contained in fiqh textbooks generally have not been classified according to their cognitive level, resulting in students having difficulty working on the questions. so it is necessary to classify the cognitive level of the question. The questions that have been classified according to the cognitive level will make it easier for the teacher to choose questions. Students will work on the questions in stages, from the easiest to the most difficult. In addition, the questions whose questions have been classified as cognitive levels will make it easier for teachers to find out the cognitive levels achieved by their students. The purpose of this study was to determine the percentage of each level of cognitive process practice questions based on Bloom's Taxonomy in the fiqh book class IV curriculum 2013. The research approach is descriptive quantitative, the method used in this study is to analyze the practice questions in fiqh textbooks. Data collection techniques with documentation. The analysis of the data used is that obtained in this study in the form of numbers which are the results of calculations through a process to get a percentage. The results showed that the Semester 2 Competency Test Questions for the Fourth Grade Jurisprudence Textbooks analyzed consisted of three cognitive processes "Remembering" (C1), "Understanding" (C2), "Applying" (C3) and the absence of questions that included cognitive level categories. C4 (Analyze), C5 (Evaluate) and C6 (Create).